2012
DOI: 10.1016/j.jvs.2011.07.097
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality of life over time among 453 patients with hyperhidrosis submitted to endoscopic thoracic sympathectomy

Abstract: The patients had an immediate improvement in QoL after ETS, and this improvement was sustained until the fifth postoperative year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 18 publications
1
59
0
3
Order By: Relevance
“…Seventeen studies, including the validation work, had a surgical intervention, 234,236,238-252 13 dermatology studies 55,57,60,[62][63][64][65][66][67]237,[253][254][255] and one quality-of-life review. 227 The tool was used in Austria (n = 6 [240][241][242]248,249,251 ), Brazil (n = 21 57,[60][61][62][63][64][65][66][67]234,[236][237][238][239]243,244,246,247,[252][253][254][255] ), Germany (n = 1 The survey response rate was 91% (344 patients). Patients included in the study suffered with either palmar and plantar (57.4%), palmar, axillary and plantar (25%), axillary (15.7%) or facial (6.5%) sweating.…”
Section: Hyperhidrosis Quality-of-life Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen studies, including the validation work, had a surgical intervention, 234,236,238-252 13 dermatology studies 55,57,60,[62][63][64][65][66][67]237,[253][254][255] and one quality-of-life review. 227 The tool was used in Austria (n = 6 [240][241][242]248,249,251 ), Brazil (n = 21 57,[60][61][62][63][64][65][66][67]234,[236][237][238][239]243,244,246,247,[252][253][254][255] ), Germany (n = 1 The survey response rate was 91% (344 patients). Patients included in the study suffered with either palmar and plantar (57.4%), palmar, axillary and plantar (25%), axillary (15.7%) or facial (6.5%) sweating.…”
Section: Hyperhidrosis Quality-of-life Questionnairementioning
confidence: 99%
“…The second, reported in Table 24, was used in sensitivity analysis. 252 Different utility assumptions associated with CS were made (see Network meta-analysis methods). The treatment following CS followed the same guideline as that for inadequate treatment response across all treatments.…”
Section: Different Levels Of Compensatory Sweating Following Endoscopmentioning
confidence: 99%
See 1 more Smart Citation
“…Wolosker et al [7] have observed that, although these patients do not present any risk for death or organ failure, the reduction in QoL can have serious consequences. In some cases, it may not only cause anxiety and distress but can also be incapacitating and even pose high risks for some professionals, such as police officers, who manipulate weapons, and electricians, who handle electric material [7].…”
Section: Diagnosismentioning
confidence: 99%
“…ETS has been used in the treatment of hyperhidrosis since the mid 1980's and several studies have shown it to be an effective treatment. 6,7 However, serious complications of this treatment occur infrequently and recurrence in the medium to long term is more common than previously believed. 6e11 The main complication of ETS is compensatory sweating reported as up to 70%, whereas, it is reported as only 5% for botulinum toxin therapy.…”
Section: Introductionmentioning
confidence: 99%